An invitation to health - Tunks, Lisa (Boston Cengage, 2023)
"Achieve a healthier lifestyle -- physically, emotionally, socially, and sexually -- with An Invitation to Health, 20th Edition. In addition to integrated, up-to-date coverage of the Covid 19 pandemic, you'll find new research on such topics as happiness and health, current statistics on life expectancy and death rates, mental health and anxiety, navigating social media, Dietary Guidelines, immunization, stress levels, safer sex practices, substance abuse, dubious diets and trendy foods, fitness monitors, vaping and cannabinoids. The book's active learning strategies offer a special focus on healthy living on a budget, taking preventive measures for healthier outcomes and implementing practical strategies that turn small changes into big benefits."
Taking charge of your health -- Emotional and spiritual well-being -- Caring for your mind -- Stress management -- Personal nutrition -- Body composition and weight management -- Physical activity and fitness -- Communicating and connecting -- Sexual health -- Reproductive options -- Sexually transmitted infections -- Major diseases -- Infectious diseases -- Consumer health -- Addictive behaviors and drugs -- Alcohol -- Tobacco and nicotine use -- Occupational and financial health -- A healthier environment -- A lifetime of health -- Answer to review questions -- Glossary -- Index.
Include index.
Keywords: Self-care, Health; Medicine, Preventive